Vietnam’s Educational Policy System in the Era of National Rise - Hoa, Dinh Thi Phuong; Son, Ngo Quang; Thuy, Ha Thi Thanh; Linh, Dao Thuy (Journal of Posthumanism, 2025)
This study uses qualitative research methods to analyze the context and conditions for the promulgation and implementation of educational policies of our country in the era of national rise, making necessary forecasts and adjustments to educational policies so that education and training can truly demonstrate its role and contribute to the socio-economic development of the country in this special context. The research results indicate: (1) there is a need for scientific research to analyze and evaluate the current status, objectives, contents, methods, and results of implementing current educational policies; (2) planning and reorganizing the system of educational policies to be synchronous, synchronized, and in line with the socio-economic policies of the country that have just been promulgated in the new era. The system of educational policies of our country in the era of national rise must: (1) aim to build a system, organization and management of education that ensures the principle of "refined, compact, strong, effective and efficient"; similar to the revolution in streamlining the apparatus and organization in the political system; (2) must be adjusted and operated towards liberating the intellectual power of scientists and teachers through revolutionary policies on science and technology, innovation but still must ensure the core and eternal principles and values of education, which is to aim at and all for the learners - a fair, creative and effective education, to serve the cause of sustainable development of the country.